Older and Wiser: Older Adults’ Episodic Word Memory Benefits from Sentence Study Contexts - Matzen, Laura E. (2013)
A hallmark of adaptive cognition is the ability to modulate learning in response to the demands posed by different types of tests and different types of materials. Here we evaluate how older adults process words and sentences differently by examining patterns of memory errors. In two experiments, we explored younger and older adults’ sensitivity to lures on a recognition test following study of words in these two types of contexts. Among the studied words were compound words such as “blackmail” and “jailbird” that were related to conjunction lures (e.g. “blackbird”) and semantic lures (e.g. “criminal”). Participants engaged in a recognition test that included old items, conjunction lures, semantic lures, and unrelated new items. In both experiments, younger and older adults had the same general pattern of memory errors: more incorrect endorsements of semantic than conjunction lures following sentence study and more incorrect endorsements of conjunction than semantic lures following list study. The similar pattern reveals that older and younger adults responded to the constraints of the two different study contexts in similar ways. However, while younger and older adults showed similar levels of memory performance for the list study context, the sentence study context elicited superior memory performance in the older participants. It appears as though memory tasks that take advantage of greater expertise in older adults--in this case, greater experience with sentence processing--can reveal superior memory performance in the elderly.